Morphology, Geologic History and Dynamics of Wimble Shoals, Rodanthe, NC - Gibbons, Ryan M (East Carolina University, 2017)
Barrier islands around the world protect estuaries and mainland areas, creating important habitat as well as environmentally and economically valuable property. Barrier islands represent 10%, of global shorelines and are often prevalent on passive margins such as the East Coast of the United States. Much of the east coast of the United States is protected by barrier island systems, and like other areas, these coastlines are dynamic, responding to storms and sea-level rise. Research of these areas is needed to aid in understanding habitats, hazards, resource availability and best management approaches. The Outer Banks of North Carolina is a strip of nearly continuous sediment, broken only by a few inlets and is an archetypal example of a wave-dominated barrier system. In many coastal studies, onshore processes of erosion and accretion have been correlated to the location of nearshore morphological features, such as ridges, shoals, and shore-oblique bars. These nearshore features are commonly used as sediment borrow sources for nearby beach nourishment projects. Wimble Shoals, offshore of Rodanthe, NC, is a major bathymetric feature that consists of five shore-oblique ridges and is adjacent to a perennial erosional hotspot area that has been the subject of a recent beach nourishment project. Although it is often reported that nearshore bathymetric features impact onshore dynamics, little is known about the nature and origin of these features, and in particular their evolution, morphology, and influence on the coast. This study aims to further our understanding of the geology and morphology of Wimble Shoals through a series of descriptive and comparative analyses involving two separate geophysical and sedimentological datasets (decadal scale). The primary objectives of this study were to examine Wimble Shoals to evaluate its morphological character, variations, onshore influence, geologic history and potential as a sand resource. Multiple methods were used to evaluate the morphology and sedimentology of both onshore and offshore areas of Rodanthe. High resolution bathymetry, slope, and backscatter was used to delineate the morphology of Wimble Shoals including subaqueous dunes, morphological ridges, and areas of outcropping. Shoreline change rates (SCR) were calculated using five digital shorelines from separate time steps (1873, 1946, 1988, 1997, and 2009). In the study region, the average long-term SCR was -0.47 m/yr with just over half of the oceanfront area analyzed showing erosion (54%). In more recent years (1997-2009), the average SCR was higher (-1.82 m/yr) with 84% of the island showing erosion. Seismic-reflection and multibeam data were used to examine the morphology of Wimble Shoals, and a comparison of data from two different time period was conducted. Decadal- and century-scale bathymetric analyses showed that Wimble Shoals is migrating southward and has some control over the areas of accretion and erosion seen in the onshore environment. Wimble Shoals is composed of highstand systems tract and lowstand systems tract sands that overly a gently dipping Pleistocene surface. The sands that compose the shoals is medium to fine-sand which is useful for adjacent nourishment projects. It is estimated that Wimble Shoals could potentially be nourishment borrow source for over 100 nourishment projects, but multiple environmental, ecological, and cultural factors need to be considered before mining these shoals.
Keywords: Shoals; Ridges; Coastal; Beach; Nourishment; Coast; Outer Banks; Wimble Shoals; Geomorphology--North Carolina--Rodanthe--History; Sedimentology--North Carolina--Rodanthe; Erosion--Research--North Carolina--Rodanthe